IMPORTANCE OF RESEARCH TO GAIN KNOWLEDGE IN HEALTH STUDENTS - Vallejo, Msc. Alida; GUZMAN, JUANA KOU; TERAN, CESAR NOBOA; ROJAS, ANA MARIA VITERI (International Journal of Research -GRANTHAALAYAH, 2020)
Research in the teaching-learning process in Higher Education Institutions is very useful to understand the issues that refer to society and the world around us. Schools should foster researchers' interest in science, as well as prepare them to envision the various applications and responsibilities of a researcher. This mission must be fulfilled from the first years of study, in all areas of knowledge, especially in the area of health. The development of scientific activity must adapt to the changes imposed by scientific, technological and innovation development. Several factors influence this process that must be analyzed. Research is considered the basis for obtaining knowledge, which will allow us to understand and find solutions to the life and health problems of the population.